Multistate unfolding of alpha-mannosidase from Canavalia ensiformis (Jack Bean): evidence for the thermostable molten globule - Kumar, Avinash; Gaikwad, Sushama M. (Biochemical and Biophysical Research Communications, 2010)
The relevance of partially ordered states of proteins (such as the molten-globule state) in cellular processes is beginning to be understood. We examined the conformational transitions in a multimeric and high molecular weight class II alpha-mannosidase from Canavalia ensiformis (Jack Bean) (Jb alpha-man) utilizing intrinsic fluorescence, solute quenching, hydrophobic dye binding, size exclusion chromatography and circular dichroism (CD) spectroscopy for the protein in presence of Guanidine hydrochloride (GdnHCl). The decomposition analysis of the protein spectra obtained during unfolding showed progressive appearance of class S, I, II and III trp. The parameter A and spectral center of mass showed multi state unfolding of the protein and phase diagram analysis revealed formation of an intermediate of Jb alpha-man in the vicinity of 1 M GdnHCl. The intermediate exhibited compact secondary and distorted tertiary structure with exposed hydrophobic amino acids on the surface, indicating the molten-globule nature. The dissociation, partial unfolding and aggregation of Jb alpha-man occurred simultaneously during chemical denaturation. The molten-globule possessed slightly higher hydrodynamic radius, perturbance in the structure up to 60 degrees C and stability of the structure up to 80 degrees C unlike the native Jack Bean alpha-mannosidase. The modes of chemical and thermal denaturation of the native protein were different. The solute quenching parameters confirmed the altered confirmation of the intermediate. Taken together, our results constitute one of the early reports of formation of GdnHCl induced molten globule in a class II alpha-mannosidase. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: alpha-Mannosidase; Circular dichroism; fluorescence; Guanidine hydrochloride; Molten globule; Thermostability; Unfolding

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.